Researching with Proximity Relational methodologies for the Anthropocene - Rantala, Outi; Kinnunen, Veera; Höckert, Emily (Arctic Encounters,, 2024)
This open access book presents a series of speculative, experimental modes of inquiry in the present times of environmental damage that have come to be known as the age of the Anthropocene. Throughout the book authors develop more nuanced ways of engaging with the environmentally vulnerable Arctic. They counter distancing, exoticising, and even apocalyptic imaginaries of the Arctic by staying proximate with mundane places and beings of the north. The volume engages and plays with familiar tourism concepts, such as hospitality, visiting, difference, care, openness, and distance, while expanding the focus from binary and human-centric approaches of hosts and guests to questions of wellbeing among multispecies communities. The transdisciplinary group of contributors share a curiosity about how staying proximate may provide theoretical depth and epistemological openings to attend to current tensions and to diversify the ways we do and enact research. Thus, each chapter provides a methodological experiment with proximity, developing diverse ways of envisioning and storying more-than-human worlds.  Outi Rantala is professor of responsible Arctic tourism at the University of Lapland, and adjunct professor of environmental humanities, at University of Turku. Her research has focused on human nature relations and engaged in creating critical, reflective, and alternative narratives on northern tourism. Veera Kinnunen is a sociologist working on a threshold of more-than-human sociology, environmental humanities, and feminist ethics. She currently works as a postdoctoral researcher at the University of Oulu. Her research interests cover dwelling with unruly more-than-human others such as microbes and waste. Emily Höckert is a postdoctoral researcher at the University of Lapland. Her research explores the multiple ways in which more-than-human hosts and guests welcome and take care of each other in tourism settings. She approaches questions of hospitality, ethics, care, and storytelling at the crossroads of hermeneutic phenomenology, postcolonial philosophy, and new materialism.